Materiality judgments on audit opinions / Takiah Mohd. Iskandar - Mohd. Iskandar, Takiah (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
Materiality is an important criterion needed for issuing an audit opinion. However, the guidance as how materiality should be judged is not clear. Research results show that "percentage effect of an item on net profit" is the most important variable in making materiality judgment. However, there is lack of consensus about what is the appropriate threshold. The objective of this paper is to study two important variables, industry type and industry specialization, that may have contributed to the inconsistencies in materiality judgments. The study also attempts to determine the specific threshold used for issuing an audit qualification. Results of an experiment indicate that the threshold for "except for" and adverse opinions are about 9% and 31% respectively. The study finds that the interaction between industry type and industry specialization affects opinion thresholds significantly at p=.004. The study shows that specialists of a particular industry differ from specialists of another industry in their opinion materiality thresholds. Hence, a consideration should be given for the inclusion of more specific guidance in the standards. In the absence of definite guidelines on the appropriate materiality thresholds, auditors have to apply their professional judgments as to the likely threshold that would be appropriate for the different types of audit opinion.